2019
DOI: 10.23940/ijpe.19.10.p16.27012708
|View full text |Cite
|
Sign up to set email alerts
|

Active Learning using Uncertainty Sampling and Query-by-Committee for Software Defect Prediction

Abstract: In the process of software defect prediction dataset construction, there are problems such as high labeling costs. Active learning can reduce labeling costs when using uncertainty sampling. Samples with the most uncertainty will be labeled, but samples with the highest certainty will always be discarded. According to cognitive theory, easy samples can promote the performance of the model. Therefore, a hybrid active learning query strategy is proposed. For the sample with lowest information entropy, query-by-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…To select uncertain samples, expected error reduction based active learning, 23 clustering‐based active learning, 24,25 and informative and representative sample‐based active learning 1,26 are proposed. In addition, Qu et al 27 proposed a hybrid active learning query strategy using uncertainty sampling and query‐by‐committee for software defect prediction 28 . Li et al 29 found that a meta‐active learning query strategy could perform better than the commonly used query strategy when a little data was labeled.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To select uncertain samples, expected error reduction based active learning, 23 clustering‐based active learning, 24,25 and informative and representative sample‐based active learning 1,26 are proposed. In addition, Qu et al 27 proposed a hybrid active learning query strategy using uncertainty sampling and query‐by‐committee for software defect prediction 28 . Li et al 29 found that a meta‐active learning query strategy could perform better than the commonly used query strategy when a little data was labeled.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, Qu et al 27 proposed a hybrid active learning query strategy using uncertainty sampling and query-by-committee for software defect prediction. 28 Li et al 29 found that a meta-active learning query strategy could perform better than the commonly used query strategy when a little data was labeled.…”
Section: Sample Selection Strategymentioning
confidence: 99%
“…There are some strategies to implement uncertainty sampling, in which the most popular sampling strategy uses entropy as an uncertainty measure [45] shown in Equation (10). Using entropy as an uncertainty measure is investigated in our prior work [46]. The reason that Entropy can be used for uncertainty sampling in active learning or in our approach as shown in Equation (11) shows that this is a metric centered on the amount of information, which can represent the amount of information needed to "encode" a distribution.…”
Section: ( ) Log( ) T Tmentioning
confidence: 99%